Biomimetic Total Syntheses of (−)‐Leucoridines A and C through the Dimerization of (−)‐Dihydrovalparicine. Issue 43 (28th August 2015) - Kokkonda, Praveen; Brown, Keaon R.; Seguin, Trevor J.; Wheeler, Steven E.; Vaddypally, Shivaiah; Zdilla, Michael J.; Andrade, Rodrigo B.
Abstract: Concise biomimetic syntheses of the Strychnos‐Strychnos‐type bis‐indole alkaloids (−)‐leucoridine A (1 ) and C (2 ) were accomplished through the biomimetic dimerization of (−)‐dihydrovalparicine (3 ). En route to3, the known alkaloids (+)‐geissoschizoline (8 ) and (−)‐dehydrogeissoschizoline (10 ) were also prepared. DFT calculations were employed to elucidate the mechanism, which favors a stepwise aza‐Michael/spirocyclization sequence over the alternate hetero‐Diels–Alder cycloaddition reaction. Abstract : Concise biomimetic syntheses of the Strychnos‐Strychnos ‐type bis‐indole alkaloids (−)‐leucoridine A and C were accomplished through the biomimetic dimerization of (−)‐dihydrovalparicine. DFT calculations were used to elucidate the mechanism, which favors a stepwise aza‐Michael/spirocyclization sequence over the alternate hetero‐Diels–Alder cycloaddition reaction.